Definition and recognition of the Deaf Linguistic Model from Veracruz - Lara Tronco, Hector Francisco; Aguilera Zárate, Raúl (IE Revista de Investigación Educativa de la REDIECH, 2023)
The Deaf Linguistic Model has been ignored by the current oralist philosophy. Through the testimonies of Deaf collaborators, we answer two questions: Who is a Deaf linguistic model? How to recognize the Deaf as a Deaf linguistic model? A regional forum, a meeting of Deaf leaders and a field exploration were carried out in five regions of the State of Veracruz: Huasteca Baja, Capital, Sotavento, Las Montañas and Olmeca. A total of 116 self-recognized Deaf Mexican Sign Language signers between the ages of 12 and 60 participated. Through an exploratory study, based on a qualitative approach with a phenomenological design and ethnographic approach, we found conceptions and elements that recognize the Veracruz Deaf linguistic model, identifying 17 Deaf adults who sign to teach Deaf adults.